Risk Factors for Canalicular Injury After Mohs Micrographic Surgery. Issue 9 (20th September 2022) - Campbell, Elliott H.; Sotelo Leon, Daniel E.; Baum, Christian L.; Wagner, Lilly H.
Abstract : BACKGROUND: There is a paucity of literature describing risk factors for canalicular injury (CI) during periocular Mohs micrographic surgery (Mohs). OBJECTIVE: This study aimed to determine factors associated with CI after Mohs. This information may inform patient counseling and surgical planning. MATERIALS AND METHODS: This case–control study compared subjects with canalicular injury after Mohs with subjects requiring ophthalmologic Mohs repair without canalicular injury. All subjects who had CI after Mohs were included in the control group. CI from other causes were excluded. RESULTS: Basal cell carcinoma was the most common etiologic tumor ( p < .00001). Canalicular injury was associated with infiltrative, morpheaform, and/or micronodular-type basal cell carcinoma. Initial tumor location involving the medial canthus was not statistically different between cases and controls (32% vs 17%, p = .22). Having a final defect involving the medial canthus region was more likely in cases versus controls (55% vs 26%, p = .01952). CONCLUSION: Although most final defects involved the medial canthal region, a substantial number of tumors resulting in CI did not initially seem to involve the medial canthus. Surgeons cannot rely simply on anatomical location when assessing risk for CI, and anticipation of need for canalicular reconstruction is challenging.